ANALYSIS OF FISHING SEASONS FOR SKIPJACK (Katsuwonus pelamis) IN THE WATERS ADJACENT TO SIBOLGA NORTH SUMATERA PROVINCE - Ramafitri Uli Arta Simarmata; Alit Hindri Yani; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aims to know the pattern of skipjack fishing seasons in the Sibolga waters North Sumatera. An analysis was conducted using skipjack production and purse seine fishing trip from the years at 2012-2016, collected by Sibolga Fishing Port.The method used is survey method and then analyzed by using the average percentage method. The result showed that the change of catch in a certain month because of the availability of fish and the succeed of fishing operation which resulted in the CPUE to fluctuate. The index of skipjack  fishing seasons can be calculated from this CPUE data. The peak of the skipjack catching season was in the western season from December to February and the least catching season occured in the transition season I from March to May. Keywords: Fishing seasons, skipjack, the average percentage methods, and CPUE